SIMULASI ALIRAN DUA FASA STRATIFIED AIR - UDARA PADA PIPA HORIZONTAL DENGAN PENDEKATAN VOLUME OF FLUID (VOF) - Yaqin, Ainul; Hudaya, Akhmad Zidni; Wibowo, Rianto (Journal of Industrial Engineering and Technology, 2024)
The flow conditions inside a pipe can involve two different densities or commonly known as two-phase flow. Besides density differences, fluctuations also affect the flow patterns of two-phase flow. These fluctuations result in various flow patterns, including the stratified flow pattern often utilized in fluid industries and the slugging flow pattern, which is generally avoided. Therefore, understanding the characteristics of these flow patterns is crucial, and Computational Fluid Dynamics (CFD) simulation methods are employed for this purpose. In the simulation model used, Volume Of Fluid (VOF) is employed with turbulent k-ε flow in a 19 mm diameter, 9 m long T-shaped pipe with a separating plate between the inlet of water and air. This setup yields various flow patterns such as Stratified ripple, Stratified wave, roll wave, and pseudo slug. At low pressure differences and velocities of JL = 0.025 m/s and JG = 1.88 m/s, a smooth stratified interface profile is observed, clearly separating the phases of water flowing continuously at the bottom and gas flowing at the top due to density differences, without any waves. As the velocities are increased to JL = 0.040 m/s and JG = 5.246 m/s, a ripple wave flow pattern occurs, characterized by small waves accompanied by long waves. Furthermore, increasing JL while decreasing JG to JL = 0.050 m/s and JG = 4.140 m/s leads to the formation of a stratified roll flow pattern, marked by long rolls, while pseudo slug flow occurs at JG = 5.246 m/s and JL = 0.076 m/s. This happens due to the increased velocity of the water phase causing the gas phase to become unstable, forming bubbles within the liquid